Earnings Quality and the Equity Risk Premium: A Benchmark Model* - Yee, Kenton K. (Contemporary Accounting Research, 2006)
Abstract This paper solves a model that links earnings quality to the equity risk premium in an infinite‐horizon consumption capital asset pricing model (CAPM) economy. In the model, risk‐averse traders hold diversified portfolios consisting of risk‐free bonds and shares of many risky firms. When constructing their portfolios, traders rely on noisy reported earnings and dividend payments for information about the risky firms. The main new element of the model is an explicit representation of earnings quality that includes hidden accrual errors that reverse in subsequent periods. The model demonstrates that earnings quality magnifies fundamental risk. Absent fundamental risk, poor earnings quality cannot affect the equity risk premium. Moreover, only the systematic (undiversified) component of earnings‐quality risk contributes to the equity risk premium. In contrast, all components of earnings‐quality risk affect earnings capitalization factors. The model ties together consumption CAPM and accounting‐based valuation research into one price formula linking earnings quality to the equity risk premium and earnings capitalization factors.